(untitled) (International Journal of Humanities and Information Technology, 2025)
Rural populations often face significant challenges in accessing timely and quality healthcare due to geographical isolation, limited healthcare infrastructure, and scarcity of specialized medical professionals. Telemedicine, defined as the remote delivery of healthcare services using telecommunications technology, has emerged as a promising solution to these challenges. This manuscript explores the potential of telemedicine in transforming rural healthcare by analyzing its benefits, limitations, and impact on patient outcomes. By reviewing current literature and presenting a mixed-methods study that combines quantitative surveys and qualitative interviews with healthcare providers and rural patients, the study demonstrates that telemedicine can reduce travel time, lower healthcare costs, and improve access to specialist consultations. However, challenges such as technological barriers, resistance to change, and issues related to data privacy persist. The paper concludes with policy recommendations aimed at optimizing telemedicine implementations to ensure sustainable and equitable healthcare delivery in rural areas